Analisis Kekasaran Permukaan Material Aluminium dengan Proses Milling Menggunakan Alat Uji Roughness Tester - Bambang Herlambang; Wawan Budiarto (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Choosing a good machine and process to make a particular product requires basic knowledge about all the possibilities that occur during the production process. Therefore, material selection, machine settings and determining appropriate machining parameters need to be optimized to produce quality products. In the milling process, surface roughness is very important. From this surface roughness, an evaluation can be made whether the workpiece is acceptabel or not. The lower the surface roughness of a workpiece, the better the quality of the workpiece. The higher the surface roughness, the lower the performance of the components of the workpiece pair will be because it will increase friction on the components of the machine elements. This research aims to determine the effect of variations in feeding work movement, spindle rotation, and feed depth on the level of surface roughness resulting from conventional milling machining processes. This research also discusses which influences produce optimal surface roughness values in conventional milling machining processes. This research was carried out three times in one combination. Data collection on surface roughness values was carried out horizontally on the surface of the workpiece by taking data three times on the workpiece. The results of the statistical analysis prove that the feeding movement variable is proven to have a significant influence on surface roughness, while the optimum combination for the lowest level of surface roughness can be obtained with a feeding movement of 249 mm/minute (3rd test)